Attitudes Towards Sleep as a Time Commitment are Associated with Sleep Regularity. Issue 6 (2nd November 2021) - Windred, Daniel P.; Stone, Julia E.; McGlashan, Elise; Cain, Sean W.; Phillips, Andrew
ABSTRACT: Objective : Irregular sleep-wake patterns are associated with poor health outcomes. However, factors that lead individuals to adopt more regular sleep-wake patterns are not well understood. This study aimed to (i) examine the relationship between sleep regularity and attitudes toward sleep in undergraduates; (ii) test an intervention to improve sleep regularity based on personalized feedback; and (iii) investigate whether changes in attitudes toward sleep associate with improved sleep regularity. Methods : Sleep-wake timing of 45 students (19.7 ± 1.8 years) was monitored daily over two weeks using an app-based diary. The least regular sleepers, calculated using the Sleep Regularity Index (SRI ≤ 81.4; N = 22), completed a four-week randomized control intervention (RCI) designed to improve sleep regularity. The Charlotte Attitudes Toward Sleep (CATS) scale was administered at baseline and post-RCI, with subscales measuring attitudes toward sleep as a time commitment (Time), and as a beneficial/enjoyable behavior (Benefits). Results : CATS Time was positively associated with SRI at baseline (r 2 = 0.16, p =.006) and during the four-week RCI (r 2 = 0.29, p =.01). CATS Benefits was not associated with SRI but was associated with sleep quality. There was no significant improvement in SRI during the intervention. The relationship between change in CATS Time and change in SRI (baseline vs. RCI) differed between intervention and control groups (r 2 = 0.27, p =.03). Conclusions : Attitudes toward sleep as a time commitment are associated with sleep regularity and should be considered as a target in future interventions aiming to improve sleep regularity.